The Great Mosque of Hohhot (Qingzhen Dasi), inner Mongolia, People’s Republic of China—more than a mosque - Soomro, Ali Raza; Azmin, Aida Kesuma (Kulliyah of Architecture and Enviromental Design, IIUM, 2015)
Great Mosque of Hohhot (Qingzhen Dasi) being the oldest mosque still erected since last four centuries in the city of Hohhot (Capital city of Inner Mongolia), P. R. China has always been important to the Muslim community there. It is undoubtedly true that the mosque should play an important role in the society and should witness many events that may involve in developing the Muslim community within their society. Mosques even during the time of prophet Muhammad Peace be upon him played several roles like; a place for worship, a place for reading, a place for negotiation, a place for treating sick persons and so on. In this regard it is very interesting to note the present roles of Great Mosque (Qingzhen Dasi) for the development of community of Muslims in the city of Hohhot. Being located in one of the remote areas of China, where Muslims in China are one of the minorities in the majority of the non-Muslims. The Great Mosque (Qingzhen Dasi) is playing tremendous roles not only for Muslims in the city of Hohhot but it is also considered as one of the important land mark as well as the urban node of the city. This paper unfolds all those tremendous roles of Great Mosque (Qingzhen Dasi) playing for the benefits of the Muslims as well as nonMuslims in the city of Hohhot and recommends conserving the Mosque for the future generations.